AN ANALYSIS OF SURGICALLY MANAGED CASES OF PELVIC ABSCESS COMPLICATING UNSAFE ABORTION - desiyun, GA Adebiyi; Ameh, Charles (Journal of Ayub Medical College Abbottabad, 2006)
Background: This study was carried out to study the demographic variables, treatment options and mortality in cases of abortion related pelvic abscess. Methods: A retrospective study of patients that had pelvic abscess as a complication of unsafe abortion. The retrieved case files were scrutinized for the necessary information. Result: The age ranged from thirteen years to forty six years, and teenagers accounted for 24.3% of the patients. About half of the patients, 51.4% were childless and parity ranged from zero to eight. The abortionists were mainly untrained personnel and the contraceptive prevalence rate was low, 5.4%. Most of the patient had conservative surgery and a significant number 94.6%, had blood transfusion. Maternal death of 18.9% was recorded with infection being the major cause. Conclusion: Unsafe abortion and its attendant complication is still a problem in Nigeria. High quality post abortion care will help a long way in saving many lives. Key words: Unsafe abortion, Induced abortion, Pelvic abscess, Conservative surgery.